Evaluation of Merdeka Teaching Platform (PMM)-Based Academic Supervision in Enhancing The Implementation of The Merdeka Curriculum and Teacher Performance in Elementary Schools - Kurniadi, Nicolas Bagas Dwi; Ismanto, Bambang (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to evaluate the effectiveness of academic supervision based on the Merdeka Teaching Platform (PMM) in enhancing teacher performance and the quality of learning in elementary schools in Semarang Regency, Central Java. Employing Kirkpatrick's four-level evaluation model—Reaction, Learning, Behavior, and Results—the study adopts a mixed-methods approach (quantitative and qualitative) through data collection techniques including pre-tests, post-tests, classroom observations, in-depth interviews, and document analysis. This study was analyzed using descriptive statistics and t-tests. The findings revealed that PMM-based supervision has a positive impact on improving teacher competencies and student learning outcomes. At SD Negeri Karanganyar 01, teacher performance scores increased from an average of 62% on the pre-test to 86% on the post-test, with a 20% improvement in student learning outcomes. At SD Negeri Kesongo 01, teacher scores rose from 58% to 84%, accompanied by an 18% increase in student achievement. At SD Negeri Delik 02, despite challenges in digital literacy, teacher performance improved from 60% to 82%, with a 15% rise in student outcomes. Similarly, at SD Negeri Candirejo, teacher scores increased from 55% to 80%, with a 16% improvement in student performance. The study concludes that PMM-based academic supervision is effective in enhancing teachers' professional competencies, particularly in designing learning activities aligned with the Merdeka Curriculum, as well as improving student learning outcomes. However, optimal implementation requires continuous assistance tailored to the unique needs of each school. The findings also recommend strengthening technology-based training, providing adequate infrastructure, and expanding PMM implementation to other schools to support the national success of the Merdeka Curriculum.